Small vs. Large Suture Bite-to-Stitch Interval for Closure of Midline Celiotomy in Cats: A Biomechanical Study - Reina Rodriguez, Fernando S.; Milgram, Joshua; Kirby, Barbara M. (Frontiers in Veterinary Science, 2020)
Abstract Objective: The objective of this study was to compare the bursting strength and characterize the mode of failure of cranial and caudal midline celiotomies closed with 2 suture patterns and an absorbable monofilament suture material. Design: Randomized, cadaveric, ex- vivo mechanical testing Sample: Feline cadavers (n= 32) Methods: Specimens were randomized into two groups based on the closure technique (small 2x2 mm or large 5x5 mm suture-bite-stitch-interval [SBSI] groups). Cranial or caudal midline celiotomies, 7.5 cm long, were created. A custom-made polyurethane bladder was inserted into the abdomen, and the celiotomies were closed in a simple continuous pattern using 3-0 polydioxanone. The repair was loaded to failure by inflating the bladder with compressed air. Bursting strength and mode of failure were recorded. Effects of body weight, gender, thickness and width of linea alba, suture-bite-stitch-interval, and location of celiotomy were analyzed using a mixed model analysis and an independent t- test, with P < 0.05 considered statistically significant. Results: There was no difference in bursting strength between cranial and caudal celiotomies. Bursting strength was lower for celiotomies closed with a large SBSI (P = 0.003). Bursting strength was greater in males compared to females (P = 0.003). Twenty five specimens failed distant from celiotomy closure, while 4 failed by fascial tearing at the site of needle penetration. Failure by loosening of the suture line with intact knots only occurred in 3 caudal celiotomies closed with a large SBSI. Gender, body weight and SBSI accounted for 61.5% of variability in bursting strength (P = 0.005). Conclusions: Small SBSI technique was mechanically superior to large SBSI when tested under these loading conditions. Clinical relevance: Supraphysiological pressures were required to cause failure in all specimens. Both small and large SBSI may be clinically applicable for midline celiotomy closure in domestic cats.